2022
DOI: 10.1021/acsami.2c04671
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Coordination Polymer for Delivery of a Subunit Broadly Acting Influenza Vaccine

Abstract: A zinc-carnosine (ZnCar) metal−organic coordination polymer was fabricated in biologically relevant N-(2hydroxyethyl)piperazine-N′-ethanesulfonic acid (HEPES) buffer for use as a vaccine platform. In vitro, ZnCar exhibited significantly less cytotoxicity than a well-established zeolitic imidazolate framework (ZIF-8). Adsorption of CpG on the ZnCar surface resulted in enhanced innate immune activation compared to soluble CpG. The model antigen ovalbumin (OVA) was encapsulated in ZnCar and exhibited acid-sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…The patterns obtained by PXRD can only be elucidated when compared to a diffractogram previously reported in literature, or as a simulated model. For example, Eckshtain‐Levi et al reported a zinc‐carnosine CP and confirmed the structure via predicted simulations of PXRD patterns (Eckshtain‐Levi et al, 2022).…”
Section: Chemical and Physical Characterization Of Cpsmentioning
confidence: 81%
See 3 more Smart Citations
“…The patterns obtained by PXRD can only be elucidated when compared to a diffractogram previously reported in literature, or as a simulated model. For example, Eckshtain‐Levi et al reported a zinc‐carnosine CP and confirmed the structure via predicted simulations of PXRD patterns (Eckshtain‐Levi et al, 2022).…”
Section: Chemical and Physical Characterization Of Cpsmentioning
confidence: 81%
“…Eckshtain‐Levi et al reports a zinc‐based CP where the organic linker is carnosine, a dipeptide that is already found in the body in high amounts in muscle tissue (Eckshtain‐Levi et al, 2022). This study adsorbed CpG to the surface of the CP and OVA encapsulated or embedded between the CP structures.…”
Section: Cps Used In Vaccine Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al prepared ZIF-8-based nanoparticles to target dendritic cells (DCs) and induce adequate immune responses as a method to provide a powerful platform against invasive malignancy and rechallenged tumors ( 19 ). In addition, ZIF-8 NPs were functionalized with poly(ethylene glycol) ( 20 ), aluminum ( 21 ), cytosine-phosphate-guanine oligodeoxynucleotides (CpG) ( 22 ), or peptides ( 23 ) that were utilized to encapsulate several antigens, such as tumor-associated antigens ( 24 ), bacterial antigens, or viruses ( 25 ), as a vaccine delivery system to enhance antigen-specific immune responses. However, few ZIF-8 NP-based adjuvants have been applied to encapsulate the PAc antigen from S. mutans to induce an immune response and protect against caries.…”
Section: Introductionmentioning
confidence: 99%